Enhanced binary Spray and Wait scheme based on reputation for DTN - Xi ZHANG; Xiao-fei WANG; Quan ZHANG; Chao-jing TANG (Tongxin xuebao)
A concept of forwarding credential was introduced,and a detection protocol of behavior was designed.A novel scheme which enhanced the prevalent binary Spray and Wait routing scheme was integrated with reputation to resist the impairment of selfishness.According to the model of bundle transferring,the determination of reputation threshold was based on probability computation.The simulation results suggest that the enhanced scheme gain an advantage over original one under selfish misbehavior.